Features of homotetrameric molecular association in protein crystals - Katre, Uma V.; Suresh, C. G. (Acta Crystallographica Section D-Biological Crystallography, 2009)
The crystal structures of proteins showing homotetrameric association, a common feature observed in many lectins, have been analyzed in order to understand the characteristics of tetrameric association in terms of the arrangement of subunits and their biological significance. The analysis could group the tetramer units into the following four categories. (i) Tetrahedral molecules, in which the four monomers form a nearly perfect tetrahedral arrangement. The angle between the axes of any two monomers is similar to 109 degrees. (ii) Molecules that form a sandwiched dimer of dimers in which the two dimers are arranged perpendicular to each other, one upon the other. (iii) Planar molecules, in which the four monomers lie in one plane and the corresponding sides of adjacent monomers face in opposite directions. This can be considered as a flattened tetrahedral shape. (iv) Planar closed molecules, in which all four monomers lie in one plane arranged in a head-to-tail fashion in a square. The first group and its variant, the third group, are the most commonly found arrangements in crystal structures. Each arrangement has its own importance for biological function. Some tetrameric assemblies that deviate from the majority described above also have relevance to their biological function.